Analisis Kinerja Supply Chain pada Agroindustri Kopi - Satria Iman Gea Putra; Fiona Niska Dinda Nadia; Eka Bambang Gusminto; Didik Pudjo Musmedi (Jurnal Ekonomi Modernisasi, 2019)
Research question’s will be answered in this study is how’s the supply chain performance of coffee processing company UD "Matt Coffee" in Bondowoso Regency. This study uses a mix method using the SCOR version 11.0. Qualitative data is obtained through observation and interviews. While quantitative data is obtained from internal parties of the company. Results showed that COGS metrics were still high, this happened in the source process. It can be concluded that if the high COGS value will reduce income. Therefore, in this study, COGS metrics were calculated up to the third mapping level to find phenomena that resulted in high COGS values ​​in the source process. This study also formulates academic and managerial implications to overcome the problems that occur on the upstream and downstream side.